A presença dos antigos em tempos de conversão: etnografia dos Kaingang do oeste paulista - Lourenço, Marília Sene de (2011)
This thesis deals with many kinds of relations between the São Paulo Kaingang and the others: their neighbours Krenak and Terena, non Indians finally, with Otherness in its Christian shape. For they‟ve chosen to articulate within their sociability another language through which persons and collectives are differencitated Catholicism and the Revivalist Churches Assembleia de Deus and Congregação Cristã no Brasil. It seems that they differenciate themselves through an oppositional process. Religious groups, political factions and extended families‟ daily oppositions, as observed through fieldwork, are brought to this text. The Jê bibliography also helps to give a sociality background to the empiric data. Hence the concepts stability and change , used as tools for the understanding of Kaingang transformations. To become a relative or an ex-relative, catholic or revivalist, an allied or an enemy these are possibilities of social action formulated by a thought that seems to be surprised by the numerous ambiguities of its own oppositional procedure. Mainly, by the ambiguity of life and death: connected to their dead relatives (the ancients), but also running away from them, the Kaingang try to solve this dilemma by all means especially in their daily life, where part of this tentative resides in conversion to Christianity.